The first published scientific study of Neurospora, including a description of photoinduction of carotenoids - David D. Perkins (Fungal Genetics Reports, 1991)
In the warm, moist summer of 1842, bread from army bakeries in Paris was spoiled by massive growth of an orange mold. A commission was set up by the minister of war to investigate the cause of the infestation and to make recommendations. Their report (Payen 1843) includes a colored plate which shows mycelia, conidia and colonies of the "Champignons rouges du pain" (called Oidium aurantiacum). I have translated one passage which concerns the effects of illumination: